Slangs Used in The Movie “Lady Bird” - Ni Putu Enik Oktaviani; I Gusti Ayu Mahatma Agung (Wanastra: Jurnal Bahasa dan Sastra, 2023)
This study aims to determine the types and meanings of slang words found in Lady Bird movie. In this study, the researchers analyzed the types of slang words based on the theory from Allan and Burridge (2006). There are five types of slang words classified by Allan and Burridge: fresh and creative, flippant, imitative, acronym, and clipping. The meaning of slang words was taken based on several online dictionaries. The research method used in this study is qualitative method. The data collection used observation method by downloading the movie script, watching the movie, and then taking note of the slang words found. The data source of this study was taken from the movie script of Lady Bird, directed by Greta Gerwig. Based on the result, there were 33 slang words found, 21 slangs were categorized as fresh and creative, 9 slang words were categorized as flippant, and 3 slang words were categorized as imitative.